An app that changes mentalities about Mobile Learning – the EduPARK Augmented Reality Activity - Pombo, Lúcia (2019)
The public usually associates mobile devices to distraction and learning disruption, and they are not frequently used in formal education. Additionally, games and parks are both associated with play and leisure time, and not to learn. This study shows that the combination of mobiles, games, and parks can promote authentic learning and contributes to changing conventional mentalities. The study is framed by the EduPARK project that created an innovative app for authentic learning, supported by mobile and augmented reality (AR) technologies, for game-based approaches in a green park. A case study of the EduPARK strategy’s educational value, according to 86 Basic Education undergraduate students, was conducted. The participants experienced the app in the park and presented their opinion about: (i) mobile learning; (ii) the app’s usability; and (iii) the impact of the educational strategy in terms of factors, such as intrinsic motivation and authentic learning. Data collection included a survey and document collection of student reflections. Data were subjected to descriptive statistics, System Usability score computing, and content analysis. Students considered that the EduPARK strategy has educational value, particularly regarding content learning and motivation. From this study emerged seven supporting pillars that constitute a set of guidelines for future development of mobile game-based learning.